The effectiveness of using distance learning in light of the Corona pandemic from the point of view of the principals of Irbid schools - Alasad, Nedal Ali (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the effectiveness of using distance learning in light of the Corona pandemic from the point of view of the principals of Irbid schools. A paragraph divided into three areas:1) Continuity of using distance education in light of the Corona pandemic.2) Obstacles to using distance education in light of the Corona pandemic.3) The desired level of distance education.The results of the study came in varying degrees: medium, high The results of the study also showed the effectiveness of the use of distance education in light of the Corona pandemic to a high degree, and the reason is that the Ministry of Education relied on the infrastructure well.Also, the continuity of the distance education process in light of the Corona pandemic came to a high degree, due to the Ministry of Education’s adoption of advance and reliable software, and the focus of teachers on social media.Moreover, the obstacles to using distance education in light of the Corona pandemic came to a high degree due to the lack of pre- prepared educational software Also, the hoped- for level of distance education in light of the Corona pandemic in the schools of Irbid Governorate ranged between a medium degree and a high degree. This result is attributed to some teachers who do not have the ability to control students’ implementation of the tests, and the interaction of teachers and students is governed by the continuous availability of Internet service.The study recommended the need to take into account the abilities and characteristics of students, the capabilities of parents and their educational level before preparing and implementing any distance education study plans, and the need to direct the departments of the Ministry of Education to the importance of developing a plan to train teachers on the distance education system in terms of the techniques used, communication tools, and their importance in This system.
Keywords: Corona pandemic; distance education; e- learning; educational platforms; educational software